Atrioventricular septal defect with anomalous systemic venous and pulmonary venous connection - Sachin Talwar; Mayank Yadav; Amolkumar Bhoje; Bharat Siddharth; Sambhunath Das; Uma Balasubramaniam; Shiv Kumar Choudhary (Journal of the Practice of Cardiovascular Sciences, 2018)
An anomalous pulmonary venous and systemic connection associated with a partial atrioventricular septal defect (AVSD) is rare. A 23-year-old patient, who presented with dyspnea and cyanosis on exertion, was found to have an anomalous pulmonary and systemic venous drainage with separate drainage of the left superior caval vein and hepatic veins into the left atrium and a partial AVSD. A patch diversion was successfully performed using two patches of glutaraldehyde-treated pericardium to create a nonobstructive pulmonary and systemic venous drainage.